Measurement of single top-quark production in association with a W boson in pp collisions at √𝑠 =13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review, 2024)
The inclusive cross section for the production of a single top quark in association with a 𝑊 boson is measured using 140 fb−1 of proton-proton collision data collected with the ATLAS detector at √𝑠 =13 TeV. Events containing two charged leptons and at least one jet identified as originating from a 𝑏-quark are selected. A multivariate discriminant is constructed to separate the 𝑡⁢𝑊 signal from the 𝑡⁢¯𝑡 background. The cross section is extracted using a profile likelihood fit to the signal and control regions and it is measured to be 𝜎𝑡⁢𝑊 =7⁢5+15−14 pb, in good agreement with the Standard Model prediction. The measured cross section is used to extract a value for the left-handed form factor at the 𝑊⁢𝑡⁢𝑏 vertex times the Cabibbo-Kobayashi-Maskawa matrix element |𝑓LV⁡𝑉𝑡⁢𝑏| of 0.97 ±0.10.
ATLAS Collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, L. Sanfilippo, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S. M. Weber, M. Wessels, J. Zinsser [und 2899 weitere]
Im Titel sind "W" und "pp" kursiv geschrieben
Gesehen am 30.06.2025